The Role of Program Financing in the System of Higher Education - George Abuselidze; Madona Mikeladze (Institute of Economic Research (IER), 2017)
The development of education in any country or society is one of the most urgent issues. When we talk about the development of education, above all we must take into consideration governmental funding system. High education and research funding is priority in most developed countries. Georgia, as the region's geopolitical and geostrategic center a few years ago began formation of the liberal democratic value-based society. Over the last period in Georgia reforms in educations system is ongoing, that led to changes in governments funding policy system. However, the higher education system is still far from Western standards of teaching and learning processes. The most significant problem in the educational system is inefficient financial management. The article above discusses the mechanisms for financing higher education in Georgia, financial management of the educational system, basically problems in program funding and their solutions. methods of studying observation, analysis and synthesis, progression from abstract towards concrete, notional experiment and experience. With the help of the article we have attempted to analyze one of the sides of the problem: how the state supports priority higher educational institutions and what the connection between consumed resources and learning outcomes is. The research clearly showed that financing education has become a priority direction for Georgia. The reform of the financing system has eliminated corruption in the educational system, increased competitiveness among the higher educational institutions, provided preparation of human resources in the fundamental fields of science and education, socially indigent population were given opportunity to get education. However, the same research also showed that the preparation of specialists with competences relevant to the modern requirements cannot be accomplished by financing only certain (though priority) programs.
Keywords: H75; I21; I22; I28; 330; Higher education; education management; budget; program financing